The current and potential role of satellite remote sensing in the campaign against malaria. (April 2016) - Kazansky, Yaniv; Wood, Danielle; Sutherlun, Jacob
Abstract: Malaria and other vector borne diseases claim lives and cause illness, especially in less developed countries. Although well understood methods, such as spraying and insecticidal nets, are identified as effective deterrents to malaria transmission by mosquitoes, the nations that have the greatest burden from the disease also struggle to deploy such measures sufficiently. More targeted and up to date information is needed to identify which regions of malaria-endemic countries are most likely to be at risk of malaria in the near future. This will allow national governments, local officials and public health workers to deploy protective equipment and personnel where they are most needed. This paper explores the role of environmental data generated via satellite remote sensing as an ingredient to a Malaria Early Warning System. Data from remote sensing satellites can cover broad geographical areas frequently and consistently. Much of the relevant data may be accessed by malaria-endemic countries at minimal cost via international data sharing polices. While previous research studies have demonstrated the potential to assign malaria risk to a geographic region based on indicators from satellites and other sources, there is still a need to deploy such tools in a broader and more operational manner to inform decision making on malaria management. This paper describes current research on the use of satellite-based environmental data to predict malaria risk and examines the barriers and opportunities for implementing Malaria Early Warning Systems enabled by satellite remote sensing. A Systems Architecture Framework analyses the components of a Malaria Early Warning System and highlights the need for effective coordination across public and private sector organizations. Highlights: Malaria and other vector borne diseases claim lives in less developed countries. Health officials need improved information on malaria risk for geographic regions. Environmental data from satellite remote sensing informs malaria risk models. Effective public and private coordination is needed to combat malaria.